2016
DOI: 10.1007/s00213-016-4275-0
|View full text |Cite
|
Sign up to set email alerts
|

The ketamine-like compound methoxetamine substitutes for ketamine in the self-administration paradigm and enhances mesolimbic dopaminergic transmission

Abstract: This study, while confirming the reinforcing effects of MXE, highlights an electrophysiological and neurochemical profile predictive of its addictive properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 65 publications
2
15
0
Order By: Relevance
“…However, MXE‐induced antinociceptive effects might involve different sites in the brain, including non‐NMDA glutamate receptors, and other (not glutamatergic) neurotransmission systems (Forman, ). Indeed, MXE displayed affinity for the 5‐HT transporter, the dopamine transporter and the noradrenaline transporter but not for σ receptors (Roth et al, ; Hondebrink et al, ), was found to significantly activate the mesolimbic dopaminergic system (Mutti et al, ) and to inhibit monoamine transporters more potently than ketamine (Hondebrink et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, MXE‐induced antinociceptive effects might involve different sites in the brain, including non‐NMDA glutamate receptors, and other (not glutamatergic) neurotransmission systems (Forman, ). Indeed, MXE displayed affinity for the 5‐HT transporter, the dopamine transporter and the noradrenaline transporter but not for σ receptors (Roth et al, ; Hondebrink et al, ), was found to significantly activate the mesolimbic dopaminergic system (Mutti et al, ) and to inhibit monoamine transporters more potently than ketamine (Hondebrink et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Rodent grooming behaviour consists of specific stereotyped patterns of sequential movements that can be affected by experimental manipulation, including administration of dopaminergic drugs (Kalueff et al, ). Given the reported stimulation by MXE of mesolimbic dopamine transmission (Mutti et al, ), we expected the time spent in self‐grooming to be increased following acute MXE administration. Thus, finding that MXE did not alter such a behaviour, even at a low dose previously showed to increase marble burying behaviour, was quite surprising.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations